“Traiani clarum saeculis exemplum” en la anécdota gregoriana - Yelo Templado, Antonio (Antigüedad y Cristianismo, 1991)
When Juan diacooo wrote the SANCTI GREGORII MAGNI VITA, in the last decades of the ninth century, he included in his writings an anglo-saxon anecdote in which (Jrcgorio remembers a pious action of the Emperor Trajano towards a poor widow y saw fulfilled his desire to be freed of the sufferings of hell. The anecdote evokes the historical tradition in regards to the justice and clemency of Trajano, and the casuistry of the liberation of a condemmed person has made the name of Trajano survive during centuries by means of the pens of innumerable theologists.